Microfinance How Bankers Could Buy Back Their Soul - Wegner, Lucia (OECD Publishing, 2006)
In order for microfinance institutions to reach more poor people they should become an integral part of the financial sector, and develop as sound domestic intermediaries. They should go commercial, broadening their client basis and scaling up their loans to small enterprises. Will it mean that they will loose their soul? Actually no; on the contrary, they will inject more soul into formal banking practices
Keywords: Development